Functional breast shield apparel a new product development - Lao, Maria Salome Salanguste 1960- (2004)
This study presents a significant breakthrough in Clothing and Consumer Education which hopes to support breastfeeding advocacy. The researcher personally designed and developed a breast shield apparel which was used to study the perception of the 97 breastfeeding mothers and 35 women with breast operation towards breast exposure/breastfeeding in public and consumers' decision making on clothing preferences. Findings will be used to improve further the innovative design/and breast openings of the apparel. Descriptive and correlational statistics were used for this experimental study. Findings revealed that breastfeeding in public is related with the type of clothes that minimized breast exposures. It also provided needed comfort to mother and child without being embarrassed in public. The apparel is also an effective means to enhance self-confidence to both groups of respondents. It was also revealed that decision-making in the choice of apparel was influenced by the respondents' lifestyle, selected product features and psychological effects of the apparel. Based on the foregoing findings, since the designs were accepted and effectively camouflaged breast/body, the breast shield apparel is hereby endorse as a support implement to local and international organizations, hospitals, and drug companies, promoting breastfeeding program; and finally, a similar study should be done on a national level. Findings have implications to the improvement of the Home Economics Education curriculum, particularly in Clothing Technology, Consumer Education and Family Studies through breastfeeding advocacy.